Affronter « les sorciers » de l’État plurinational. La dimension occulte du conflit entre Potosí et le gouvernement de Morales (2015-2019) - Pascale Absi (Cahiers des Amériques Latines)
In July 2015, the town of Potosi began the longest blockade in its history to denounce the recurrent lack of public investment. While discussions with the Morales government had been broken off, the rumour spread of the arrival in Potosi of witches hired by the authorities to temper the zeal of the dissatisfied population. Under the leadership of three women healers, a group of inhabitants decided to launch an attack from the top of the surrounding mountains and the cemetery to counter the attack by the president’s witches. They resumed their hostilities in October 2019 after the controversial presidential elections. The purpose of this article is to show that the recourse to witchcraft attributed to the Bolivian President and the ritual responses could be analysed as a political and moral commentary on the state, in the context of the erosion of Evo Morales’s popularity and legitimacy.